Elderly Dementia Patient with Recurrent Respiratory Failure due to the Abuse of a Fentanyl Patch: A Case Report - Yuki Tateno (Global Journal of Anesthesiology - Peertechz Publications, 2016)
I experienced the case of an elderly patient with dementia who had recurrent respiratory failure due to the abuse of a transdermal fentanyl patch. Opioids have been recently used in patients with moderate-to-severe chronic non-cancer pain and in those with cancer pain in palliative care [1]. A transdermal fentanyl patch has been reported effective for the treatment of chronic cancer and non-cancer pain [2]. However, previous reports showed the life-threatening toxicity of respiratory repression from the use of a fentanyl patch. It usually occurred when the dosage or absorbed amount was excessive either by accident or design [3,4].